Irregular migration struggles and active subjects of trans-border politics: New research strategies for interrogating the agency of the marginalised. (August 2017) - Strange, Michael; Squire, Vicki; Lundberg, Anna
The politics of migration has become increasingly prominent as a site of struggle. However, the active subjecthood of people on the move in precarious situations is often overlooked. Irregular migration struggles raise questions about how to understand the agency of people who are marginalised. What does it mean to engage people produced as 'irregular' as active subjects of trans-border politics? And what new research strategies can we employ to this end? The articles presented in this Special Issue of Politics each differently explore how actions by or on behalf of irregular/ised migrants involve processes of subjectivity formation that imply a form of agency. Collectively we explore how irregular migration struggles feature as a site marked by active subjects of trans-border politics. We propose a research agenda based on tracing those processes – both regulatory, activist, and everyday – that negotiate and contest how an individual is positioned as an 'irregular migrant'. The ethos behind such research is to explore how the most marginalised individuals reclaim or reconfigure subjecthood in ambiguous terms.